Functional Polymorphisms in DNA Repair Genes Are Associated with Sporadic Colorectal Cancer Susceptibility and Clinical Outcome - Jiraskova, Katerina; Hughes, David J; Brezina, Stefanie; Gumpenberger, Tanja; Veskrnova, Veronika; Buchler, Tomas; Schneiderova, Michaela; Levy, Miroslav; Liska, Vaclav; Vodenkova, Sona; Di Gaetano, Cornelia; Naccarati, Alessio; et al. (International journal of molecular sciences, 2018)
DNA repair processes are involved in both the onset and treatment efficacy of colorectal cancer (CRC). A change of a single nucleotide causing an amino acid substitution in the corresponding protein may alter the efficiency of DNA repair, thus modifying the CRC susceptibility and clinical outcome. We performed a candidate gene approach in order to analyze the association of non-synonymous single nucleotide polymorphisms (nsSNPs) in the genes covering the main DNA repair pathways with CRC risk and clinical outcome modifications. Our candidate polymorphisms were selected according to the foremost genomic and functional prediction databases. Sixteen nsSNPs in 12 DNA repair genes were evaluated in cohorts from the Czech Republic and Austria. Apart from the tumor-node-metastasis (TNM) stage, which occurred as the main prognostic factor in all of the performed analyses, we observed several significant associations of different nsSNPs with survival and clinical outcomes in both cohorts. However, only some of the genes (REV3L, POLQ, and NEIL3) were prominently defined as prediction factors in the classification and regression tree analysis; therefore, the study suggests their association for patient survival. In summary, we provide observational and bioinformatics evidence that even subtle alterations in specific proteins of the DNA repair pathways may contribute to CRC susceptibility and clinical outcome.
Keywords: DNA-dependentní DNA-polymerasy; Polymorphism, Single Nucleotide; DNA-Binding Proteins; Humans; colorectal cancer susceptibility; lidé středního věku; DNA vazebné proteiny; analýza přežití; oprava DNA; kohortové studie; jednonukleotidový polymorfismus; N-glykosylhydrolasy; Aged; Female; dospělí; DNA repair genes; senioři; lidé; DNA-Directed DNA Polymerase; přežití bez známek nemoci; Rakousko; Survival Analysis; Cohort Studies; DNA Repair; Adult; Austria; N-Glycosyl Hydrolases; Neoplasm Metastasis; metastázy nádorů; ženské pohlaví; kolorektální nádory; Male; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; functional single nucleotide polymorphism; Czech Republic; Odds Ratio; Disease-Free Survival; Česká republika; mužské pohlaví; DNA Polymerase theta; odds ratio; survival analysis; Colorectal Neoplasms; DNA-polymerasa theta